The Pap-Smear Test Experience of Women in Turkey: A Qualitative Study - Ozsoy, Suheyla; Arabaci, Zeynep (Asian Pacific Organization for Cancer Prevention, 2012)
The study was planned with the purpose of examining the attitude of women who have pap-smear test for the early diagnosis of cervical cancer, factors affecting their decisions and their feelings and experiences during this period.A phenomenological method was used. Data were collected between March 2012 and April 2012 using standard and purposive samplings from 17 women. A detailed interview with women were held in their houses and recorded. The data collection tool consisted of two parts, one of which is information form with 17 questions identifying sociodemographic and cervical cancer risk factors of women and the second part is made up of semi-structured interview form with 15 alternative questions taking literature and the pap-smear test into consideration. Collected data were put into a written document. Content analysis was held by loading the documents into NVIVO 8 Statistical Programme.The study comprised themes such as cervical risk factor, decision of taking pap-smear test, taking pap-smear test, knowledge about pap-smear test, relieving factors during pap-smear test, obstructive factors during pap-smear test, gynecological examination and feelings of women during and after pap-smear test while waiting for the results.As women perceive gynaecological examinations differently from other examinations, they have different feelings in each process of the Pap smear test. Medical staff should advise women more clearly on the nature and advantages of the Pap-smear test.
Keywords: Adult; Vaginal Smears; Health Knowledge, Attitudes, Practice; Turkey; pap smear test; Data Collection; Decision Making; Health Behavior; qualitative study; Uterine Cervical Neoplasms; Middle Aged; Prognosis; Early Diagnosis; Patient Education as Topic; Cervical cancer; Humans; Female; women; Physical Examination; Qualitative Research; Papanicolaou Test; 3. Good health; 5. Gender equality